A Structural Framework for Distributed Electronic Voters Register - Etuh, Emmanuel; Zayyanu, Umar; Jacob, Onyebuchi Destiny (Journal of Information, 2019)
Electronic Voters Register is a key deliverable of the pre-voting stage in an E-voting system that has become a key component of governance in this 21st century. E-voting system is generally grouped into three phases: before-voting, during-voting and after-voting phase. Before-voting handles the enlistment of eligible voters into the voters’ database which is a determinant factor for a successful election. Just being enlisted is not a guarantee that a registered voter will participate in an election unless the voter is present at the particular polling unit where the voter registered, on account of change of location, the voter must request for transfer of data to the new location before the election to qualify for voting. So many voters have been disenfranchised due to inevitable relocation which poses a serious challenge in the efficiency of the voters register. This has greatly reduced the total number of eligible voters in the existing system. The Purpose of this research is to design a structural framework that eliminates the hurdles voters go through to become eligible to elect their preferred candidate. Once the Direct Data Capture (DDC) system registers a voter at each polling unit, a locally distributed database across all the registration centers collate and transmit the data to the central database through the States thereby eliminating duplicates from any quarter, redundancy, and need for transfer request as a result of migration. The most suitable approach is the distributed database model that implements a tree data structure for efficient electronic voters register.